Soybean Yield and Nutrient Utilization following Long‐Term Pelletized Broiler Litter Application to Cotton. (1st May 2015) - Adeli, Ardeshir; Read, John J.; McCarty, Jack; Jenkins, Johnie N.; Feng, Gary
Abstract : Broiler ( Gallus gallus domesticus ) litter may have long‐lasting plant growth benefits after application is terminated. This study determined residual effects of pelletized litter applied to cotton ( Gossypium hirsutum L.) on yield and nutrient utilization of soybean [ Glycine max (L.) Merr.]. Treatments were replicated three times. Treatments included pelletized broiler litter subsurface banded to cotton at the rate of 6.7 Mg ha −1, urea‐ammonium nitrate (UAN solution) injected at the rate of 134 kg N ha −1 and unfertilized control in three previous years (2008–2010). Soybean planted in 2011, 2012, and 2013, and provided no additional litter or fertilizer. Soybean height was determined at 28, 42, 56, 71, 86, 102, and 115 d after planting. Total aboveground biomass, leaf area index (LAI) and plant nutrient concentrations were determined at growth stage R5. Soybean yield and plant nutrient concentrations were greater in pelletized litter than fertilizer N treatments. Soybean plants in plots received pelletized litter were significantly ( P < 0.05) taller and had greater leaf area than the fertilizer N and control plots. Total aboveground biomass at R5 did not differ between pelletized litter and fertilizer N treatments; however grain yield was greatest for residual litter treatment. In 2011, soybean grain yield and grain N, P, and K uptake were significantly greater in plots received pelletized litter, as compared with fertilizer N and control plots. Residual effects of pelletized broiler litter in cotton increased soybean production for 1 yr and influenced soil fertility for several years beyond the year of application.